Mechanisms underlying the promotion of papillary thyroid carcinoma occurrence and progression by Hashimoto’s thyroiditis - Xue, Xiaohui; Wu, Deqi; Yao, Hangyu; Wang, Kainan; Liu, Zhengtao; Qu, Haijiang (Frontiers in Endocrinology, 2025)
Hashimoto’s thyroiditis (HT) and papillary thyroid carcinoma (PTC) co-occurrence raises significant questions regarding the immune microenvironment and molecular mechanisms in thyroid tumor development. This review synthesizes recent literature to explore the immune microenvironment and molecular characteristics of PTC patients with HT, and to analyze how these characteristics influence disease onset, progression, and treatment. We focused on the immunological and molecular biological mechanisms underlying the interaction between HT and PTC, particularly the recruitment and activation of immune cells and alterations in key signaling pathways. Studies indicate that PTC with HT exhibits distinctive immune microenvironmental features, such as the role of regulatory T cells (Tregs), activation of the IFN-γ-mediated CXCR3A-CXCL10 signaling axis, and NF-κB pathway activation. Additionally, thyroid-stimulating hormone (TSH) stimulation, RET/PTC gene rearrangements, and changes in STAT6 and DMBT1 gene expression levels also play significant roles in PTC development. Notably, while HT may increase the risk of PTC, patients with concurrent HT tend to have better prognoses. Future research should further elucidate the complex interplay between these two diseases to prevent the transformation of HT into PTC and offer more personalized treatment plans for PTC patients, including considerations for preoperative thyroidectomy and lymph node dissection strategies, as well as postoperative TSH suppression therapy risk assessment. This review underscores the importance of a deeper understanding of HT and PTC interactions and offers new perspectives for future research directions and therapeutic strategies.